2015
DOI: 10.1016/j.ijcard.2015.02.023
|View full text |Cite|
|
Sign up to set email alerts
|

Telemedicine for cardiovascular disease continuum: A position paper from the Italian Society of Cardiology Working Group on Telecardiology and Informatics

Abstract: Telemedicine is the provision of health care services, through the use of information and communication technology, in situations where the health care professional and the patient, or 2 health care professionals, are not in the same location. It involves the secure transmission of medical data and information, through text, sound, images, or other forms needed for the prevention, diagnosis, treatment, and follow-up of a patient. First data on implementation of telemedicine for the diagnosis and treatment of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 62 publications
0
30
0
1
Order By: Relevance
“…Cardiology is a promising area in telemedicine and, within cardiology, acute coronary syndrome (ACS) care is one of the fields where most of the efforts have been made. 5 In this context, telemedicine strategies have the potential to improve diagnosis and to increase healthcare professionals' adherence to the therapeutic measures established for ACS, thus improving ACS care. The current evidence has largely been centred on the validation of technologies, feasibility, usability or the impact on process outcomes, but there are paucity of data on the impact on patient-centred outcomes to justify implementation of telemedicine.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiology is a promising area in telemedicine and, within cardiology, acute coronary syndrome (ACS) care is one of the fields where most of the efforts have been made. 5 In this context, telemedicine strategies have the potential to improve diagnosis and to increase healthcare professionals' adherence to the therapeutic measures established for ACS, thus improving ACS care. The current evidence has largely been centred on the validation of technologies, feasibility, usability or the impact on process outcomes, but there are paucity of data on the impact on patient-centred outcomes to justify implementation of telemedicine.…”
Section: Introductionmentioning
confidence: 99%
“…Practitioners support an extensive use of telemedicine (e.g. promoting cooperation, information sharing, decision support and flexibility) especially for those with chronic conditions, thus improving the quality of care [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews have found consensus on the effectiveness of telemedicine devices in patients with chronic heart failure and coronary heart disease [12][13][14][15][16]. The benefits of telemedicine in cardiology include reduced mortality and number of hospital admissions, rationalized costs and improved practitioners' decision making [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the absence of a TM legal and regulatory framework at national level remains the main problem. For this reason, both in the year 2009 82 and more recently 83 a position paper on TM was published by the Italian Society of Cardiology to better define operational standards starting from the Italian best practice on TM. In 2014, the national strategic guidelines on TM were published by the ‘State-Regions Conference’ 84 .…”
Section: Technical and Regulatory Affairsmentioning
confidence: 99%